SOCIOCULTURAL ASPECTS REPRESENTATION: A CONTENT ANALYSIS ON AN EFL E-TEXTBOOK FOR THE TWELFTH GRADERS IN INDONESIA - ., PUTU CANDRAWATI; ., Prof. Dr.I Ketut Seken,MA; ., Prof. Dr. Putu Kerti Nitiasih, MA (Jurnal Pendidikan Bahasa Inggris, 2014)
This study aimed at analyzing representation of ten sociocultural sub aspects, namely: age; gender; social distance and status; politeness strategies; genres; registers; major dialects; and Background Knowledge of the Target Language Group (BKTLG) and Crosscultural Awareness (CcA), in an e-textbook, Developing English Competencies (DEC). Discourse Qualitative Content Analysis was the research method and DEC was the data corpus. Data were gathered through e-textbook observation and were analyzed quantitatively and qualitatively. Findings showed that: age group of >12-18 years contributed 40% of the total 117 units; 1.098 units signified man, and 321 units were of women; 71% of conversational texts showed intimate social distance and the rest 29% indicated distant one; negative politeness strategies were employed most often (40.12%); non-drama/prose/poetry genres occupied 66% of the entire units; informal words and/or expressions were the most frequently appeared register; British English dialects gained 70% of the total 197 occurred units; 62% of the texts were BKTLG-related, leaving the rest 38% of them CcA-related. Qualitatively, all sub aspects were interconnected, creating a tight sociocultural entity. keyword : e-textbook, Indonesia, representation, sociocultural aspects, twelfth graders